Interconnected interface enhanced electrical properties of graphite in bio-based epoxy from insulating to conductor composites - Mohd Rus, Anika Zafiah (2015)
The fabrication and characterization of composite films of graphite/bioepoxy is disclosed. Thin films of ~0.1 mm thick are prepared using a simple solution mixing with mass proportion of 1/0.5 (biomonomer/Methylene Diphenyl Diisocyanate, MDI), upon differ treated graphite weight loading (5 wt.%, 10 wt.%, 15 wt.%, 20 wt.%, 25 wt.%, 30 wt.%) and drop casting at room temperature. The morphologic study by FE-SEM shows a homogeneously dispersed and strong interface between the graphite and the bioepoxy material. Ultraviolet-visible (UV-vis) spectrophotometer are performed to evaluate the changes in adsorption spectra arising with the increasing of graphite weight loading (wt.%) into the bio-based matrix. An eye opening I-V characteristic of the thin films where the percolation threshold occurs at higher graphite loading (20 wt.%, 25 wt.% and 30 wt.%) gives conductivity of 103-104 S/m. Whilst lower graphite loading (5 wt.%, 10 wt.% and 15 wt.%) somehow need further discussion. The influence of graphite in bioepoxy materials is paramount as it across insulatingsemiconductor-conductor applications.